ANALISIS PENERAPAN PRINSIP EKONOMI SYARIAH PADA UMKM MIE PANGSIT LISA DI KOTA MEDAN - Sanjai Kurniawan Lubis; Rolan Rizki Rinaldi Daulay; Riza Aulia; Zainarti Zainarti (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The application of sharia economic principles in the Micro, Small, and Medium Enterprises (MSMEs) sector is a crucial aspect in creating fair, ethical, and sustainable business practices. This study aims to examine the extent to which sharia economic principles are applied in the operational activities of the Mie Pangsit Lisa MSME, located in Medan City. The analysis focuses on the production process, transaction mechanisms, pricing systems, and work relationship patterns between business owners and employees. This study used a field research method with a descriptive qualitative approach. Data were obtained from primary and secondary sources through direct observation, in-depth interviews, and documentation. Data analysis was conducted descriptively and analytically to describe the actual conditions in the field. The results indicate that the Mie Pangsit Lisa MSME has implemented most of the values and principles of sharia economics, particularly in the aspects of product halalness, transaction honesty, and price fairness. However, several aspects still require strengthening, particularly in the understanding and application of sharia principles more comprehensively to achieve optimal sharia principles.